2001
DOI: 10.4049/jimmunol.167.8.4593
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose Leptin Activates Human Leukocytes Via Receptor Expression on Monocytes

Abstract: Leptin is capable of modulating the immune response. Proinflammatory cytokines induce leptin production, and we now demonstrate that leptin can directly activate the inflammatory response. RNA expression for the leptin receptor (Ob-R) was detectable in human PBMCs. Ob-R expression was examined at the protein level by whole blood flow cytometry using an anti-human Ob-R mAb 9F8. The percentage of cells expressing leptin receptor was 25 ± 5% for monocytes, 12 ± 4% for neutrophils, and 5 ± 1% for lymphocytes (only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
183
2
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(205 citation statements)
references
References 40 publications
9
183
2
11
Order By: Relevance
“…[19][20][21] A deficiency of leptin is responsible for severe impairments of both innate and acquired immunity, including the differentiation and activation of NK cells. 22 During the early phase of metastasis, cancer cells are recognized and destroyed by the host's immune system, especially by NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] A deficiency of leptin is responsible for severe impairments of both innate and acquired immunity, including the differentiation and activation of NK cells. 22 During the early phase of metastasis, cancer cells are recognized and destroyed by the host's immune system, especially by NK cells.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc repletion in previously deficient subjects appears to upregulate the production of Th1-systemic cellular host defense proinflammatory cytokines including tumor necrosis factor (TNF)-a (Beck et al, 1997). In addition, zinc supplementation seems to promote the secretion of leptin (Mantzoros et al, 1998) and in humans, it has been shown that leptin can increase TNF-a and IL-6 production by peripheral blood mononuclear cells and monocytes (Zarkesh-Esfahani et al, 2001). TNF-a exerts a strong inhibitory effect on myosin expression in muscle cells (Acharyya et al, 2004) and is implicated in the pathophysiology of anorexia; these two mechanisms could lead to wasting.…”
Section: Zinc Supplements Among Hiv-infected Women E Villamor Et Almentioning
confidence: 99%
“…6 Leptin is now known to have potent immunomodulatory actions. 7 Interactions between leptin and its receptors on immune cells regulate immune cell functions, 8,9 including phagocytosis 10 and cytokine production. 11 Leptin deficiency also sensitizes T cells to corticosteroidinduced apoptosis, which promotes thymic atrophy in ob/ob mice.…”
mentioning
confidence: 99%